Тестируемый как подсистема замкнутого контура регулирования - Ризун, Н. О. (НТУ "ХПИ", 2012)
Обоснованы вид и содержание параметров математической модели тестируемого как подсистемы замкнутого контура регулирования, адекватно описывающей его реакцию на тестовые задания в соответствии с уровнем профессиональной подготовленности.

The form and content of the parameters of the mathematical model testee as a subsystem of the closed contour of regulation, adequately describing his/her reaction to the test tasks based on the objective level of professional readiness was grounded.
Testee as a subsystem of closed contour of regulation
Keywords: математическая модель; тестовые задания; реакция; профессиональная подготовленность; parameters; mathematical model; contour of regulation; professional readiness; test tasks